(3GdBKGQ GdYdhjIs - (3eMeO Hf CMeO Hf eMeO Hf QTO GdbQWHj GdCfOdSj, CHh GdhdjO (B((3GdMajO(B)(3,J (B595 (3g` s
(3ChdgG (B:s
(3GHJO ChdkG ai gPG GdcJGH HPcQ ZQV cJGH eKd GdcJH GdJi SHbJ s
(3BNQgG (B:s
(3ajfHZi Cf jchf GdfXQ ajg HYO GdZGA s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3eUOQ GbJfGA GdCUd (B:s
(3CSGfjG (B- (3eOQjO s
Keywords: (3GdadSaI hGdefWbs